Locational, neighborhood, structural and socio-cultural attributes of housing in homeownership decisions - Tan, Teck-Hong * (2012)
The sharp increase in house prices has brought government and housing developers to take close attention to the housing need of first-time homebuyers by supplying quality affordable housing to them through PR1MA housing scheme. The goal of this paper is to determine the right housing attributes required by potential first-time homebuyers which will ensure this affordable housing scheme gets off the right footing. A total of 300 questionnaires were distributed to potential first-time homebuyers in Klang Valley, Malaysia but only 265 questionnaires were returned. Results revealed that accessibility and guarded neighborhood influence homeownership preferences by first-time homebuyers. It also showed that first-time homebuyers were receptive to environmentally-sensitive homes. However, socio-cultural attributes of housing exert less influence on homeownership decisions.